Profile of Technological Pedagogical And Content Knowledge (TPACK) Middle School Teachers in Sekarbela District, Mataram City - Ismail Ismail; Muhammad Muhammad; Bahtiar Bahtiar (Department of Physics Education, Universitas Mataram, 2022)
Teachers with TPACK perspectives are teachers who understand the correct pedagogy and conceptual understanding by using technology in teaching subject matter. By having the right TPACK, teachers will be able to engage and motivate students in exploring learning content to a greater extent. This study examines the TPACK profile of junior high school teachers in the Sekarbela sub-district of Mataram city using the TPACK framework. This research is ex-post-facto research and causal associative research with a quantitative approach. The population in this study were junior high school teachers in Sekarbela District, Mataram City, totaling 120 teachers, with a sample of 60 teachers who were taken using a proportional random sampling technique. The data collection technique used questionnaires and documentation, while the data analysis technique used multiple regression using SPSS for windows 21. The results showed that the component of Technological Content Knowledge scored 36.50, which fell into the low category. Pedagogical Knowledge (PK) got a score of 54.80, Technological Knowledge (TK) got a score of 40.83, Content Knowledge (CK) got a score of 47.97, and Technological Pedagogical Knowledge fell into the medium category. Meanwhile, Pedagogical Content Knowledge (PCK) scored 60.93, and Technological, Pedagogical, and Content Knowledge (TPACK) scored 63.53, which fell into the high category. Hence, it can be concluded that the research results show the average overall ability of teachers in the seven TPACK frameworks has a score of 50.07 within high criteria.